Gallery Walk+Peer Talk in Language Testing and Assessment: Students’ Perspectives - Sarwanti, Sri (JOLLT Journal of Languages and Language Teaching, 2020)
A useful conceptual understanding of ZPD can benefit the students from having  talks with others in increasing their capability of knowing something. This idea of social constructivism underpins the need for opportunities for collaboration and support, and for learning. Individuals are required to construct self-knowledge and develop new perspectives, by engaging in hands-on activities rather than using structured information. If peer talk is combined with gallery walk where the students have the opportunity to share ideas, the combination bears such an active class activity. This study reveals the students’ achievements on how they negotiate their problems through conversing with each other. The problem-based conversation plays among students themselves in their initial academic development. This study supports theory highlighting the importance of talk in social interaction as a prerequisite for increasing students’ achievement. The results of this study show that the combination of gallery walk-peer talk able to improve the students’ achievements and also the students’ participation in class. The results also uncovers why they enjoy learning by doing gallery walk-peer talk.